EFFORTS TO IMPROVE STUDENTS' LEARNING ACTIVITIES THROUGH CLASS CONCERN TYPE ACTIVE LEARNING STRATEGY IN THE CLASS VIII FIQH SUBJECT AT MTS ITTIHADIL UMMAH KARANG ANYAR PAGESAN TIMUR MATARAM - Juliatun (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
The purpose of this study was to determine how the implementation of the active learning strategy of class concern type to improve student learning activities in the subject of fiqh class VIII at MTs Ittihadil Ummah Karang Anyar Pagesangan Timur Mataram in the 2016/2017 Academic Year. The type of research used is classroom action research (CAR) with the research subjects of class VIII students totaling 14 students consisting of 9 males and 5 females. This study was conducted in two cycles consisting of the planning, implementation, observation, and reflection stages. Student learning activities and teacher activities were taken using observation sheets. While student learning outcome data through tests given at the end of each cycle. The data obtained from the test results were then analyzed using descriptive statistics, namely to find the percentage of individual student learning completeness and classical completeness. The results of data analysis showed that from cycle to cycle there was an increase. The results of the study showed that in cycle I, the results of observations of student learning activities were 39% categorized as less active and teacher activities 60% categorized as quite good. In cycle II, student learning activities increased to 71% categorized as active and teacher activities 79% categorized as good. The analysis of the evaluation results in cycle I achieved an average score of 69.54 and a classical completion percentage of 54.54% of 14 students, only 11 people took the test, 6 people completed and 5 people did not complete. From the average score and the classical completion percentage, it is still low and has not reached the specified target. In cycle II, the evaluation results obtained increased with an average score of 76.53 and a classical completion percentage of 85%. Of the 14 students, only 13 students took the test, 11 people completed and 2 people did not complete. From the data obtained, it can be concluded that the use of the class concern type active learning strategy can improve student learning activities in the subject of Islamic jurisprudence for class VIII at MTs Ittihadil Ummah Karang Anyar Pagesangan Timur Mataram in the 2016/2017 Academic Year.